Digital financial innovation's urgency for micro, small, and medium-sized entrepreneurs (an empirical case study of Indonesia) - Lucky Nugroho; Timea Gal; Nirdukita Ratnawati; Soeharjoto; Audita Setiawan (IAEI, 2023)
The development of information technology, computers, and the internet is something that cannot be avoided and has become part of daily activities, including trade transactions. Therefore, the purpose of this conceptual paper is to determine the role of financial technology in supporting trade transactions among micro, small, and medium entrepreneurs (MSMEs). The method used is descriptive-qualitative, which aims to answer the formulation of the problem consisting of (i) What is the role of financial technology in supporting digital trade; (ii) What are the benefits of financial technology for MSME business transactions? The results of this conceptual paper are: (i) the use of financial technology, also known as fintech, in supporting digital sales or e-commerce is very important in facilitating online shopping and accelerating business growth and digital trade; (ii) financial technology (FinTech) can provide many benefits for micro, small, and medium enterprises (MSMEs). The implication of this conceptual paper is to provide information and a reference for stakeholders who are concerned about MSMEs and financial technology. The novelty of this conceptual paper is that it discusses financial technology and its benefits for MSMEs, which are still rarely discussed